NILAI-NILAI PENDIDIKAN AKHLAK DALAM NOVEL SURGA YANG TAK DIRINDUKAN - Rizal Ilham Ramadhan; Santi Lisnawati; Salati Asmahasanah (KOLONI, 2022)
The value content of a literary work is an essential element of the work as a whole. Disclosure of the values ​​contained in a literary work, will not only provide an understanding of the socio-cultural background of the narrator, but also contain the ideas and moral values ​​in the novel Paradise that is not to be missed. The purpose of this study was to find out the values ​​of moral education, lessons and wisdom in the Unmissable Heaven novel. The method used in this study is a qualitative method or library research. Qualitative research method is research based on the philosophy of postpositivism and is used to examine the condition of natural objects (the opposite is experiment), the researcher is the key instrument, the data source is carried out purposively and snowball, and research results emphasize more on meaning than generalization. For qualitative research, the type of library research or library study, the systematic writing used is the Research Method Approach, Data and Data Sources, Data Collection Techniques and Procedures, Data Analysis. The results of this study indicate that the moral values ​​in the novel paradise that are not missed are morals, sincerity, gratitude, good deeds, and gentleness. Wisdom is a reflection and seriousness of utilizing knowledge and events. And look at the relationships or links that exist in it and discuss the source and purpose. Keywords: Values, Education, Morals, Works, Novels, Wisdom